Arthroscopic Meniscectomy Versus Meniscal Repair: A Comparative Functional Outcome Study - Hossain, Mohammad Kamal; Alam, Md Shamsul; Rahman, Sk Muhammad Atiqur; Hossain, Md Saklayen; Salauddin, Md Ashik (Journal of Rangpur Medical College, 2026)
Background: Meniscal tears are among the most common knee injuries, leading to pain, swelling, and functional limitations that can significantly affect daily activities and athletic performance. Objective: This study aimed to evaluate and compare the functional outcomes of arthroscopic partial meniscectomy and meniscal repair using validated clinical scoring systems. Methods: This prospective comparative study was conducted at the Department of Orthopaedic Surgery, National Institute of Traumatology & Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh, from July 2024 to June 2025 on 64 patients diagnosed with symptomatic meniscal tears requiring surgical intervention divided into two equal groups: arthroscopic partial meniscectomy (n=32) and meniscal repair (n=32). Patients were followed up at 3, 6, and 12 months postoperatively, and final functional outcomes were assessed using the same scoring systems applied preoperatively. Data were analyzed using SPSS version 25.0. Results: Preoperative IKDC, Lysholm, and Tegner scores were comparable between groups. At final follow-up, the repair group achieved higher mean IKDC (85.9 vs 78.4, p-value=<0.001), Lysholm (90.4 vs 82.6, p-value=<0.001), and Tegner (6.3 vs 5.1, p-value=0.002) scores. Excellent functional outcomes were observed in 62.5% of repair patients versus 37.5% of meniscectomy patients. Complications were low in both groups, with slightly higher reoperation rates in the repair group (9.4% vs 3.1%). Conclusion: Although both arthroscopic partial meniscectomy and meniscal repair lead to significant improvements in knee function for patients with meniscal tears,meniscal repair provides superior functional outcomes, higher activity levels, and a greater proportion of excellent results at final follow-up. J Rang Med Col.2026 Mar;11(1): 73-77